Oxidative Stress-Induced Endothelial Dysfunction Contributes To Cardiovascular Disease - Maria Giovanna Scioli; Federico D'Amico; Roger Rodríguez Guzmán; Ela María Céspedes Miranda; Augusto Orlandi (Revista Cubana de Investigaciones Biomédicas, 2019)
Objective: Oxidative stress is supposed to be involved in cardiovascular pathology through vascular cell damage. Identification of oxidative stress markers can represent a method for early diagnosis of vascular dysfunction. Biomolecular mechanisms of the vascular damage remain partially understood. Material and Methods: In vitro and ex vivo studies were performed in order to investigate the role of oxidative stress and the potential preventive action of antioxidant agents against activation, proliferation and/or apoptosis of human endothelial and vascular smooth muscle cells. The expression and activity of oxidative stress enzymes, reactive oxygen species and O2- radicals, including NADPH oxidase isoforms were evaluated, as well as leukocyte adhesion assay and the expression of cell adhesion molecules. In addition, histological and immunohistochemical analysis of human aorta tissue were performed. Results: We detected higher levels of oxidative stress markers during endothelial activation and leukocyte recruitment. In addition, oxidative stress was involved in the modulation of cell proliferation, vascular smooth cell phenotype, and cell apoptosis. Vascular and endothelial dysfunction by oxidative stress was mediated by NADPH oxidase 4 activity. The treatment with antioxidant agents such as ascorbic acid, NAC and NADPH oxidase 4 specific inhibitors prevented oxidative stress-induced vascular and endothelial dysfunction. Conclusion: We demonstrated that oxidative stress is pivotal in vascular and endothelial dysfunction. Moreover, our data provide additional information about the role of oxidative stress in the pathogenesis of cardiovascular disease. The identification of those oxidative stress markers in vascular cells will allow an early diagnosis and an appropriate antioxidant therapeutic approach.